2020
DOI: 10.1136/fmch-2020-000406
|View full text |Cite|
|
Sign up to set email alerts
|

Clinicopathological characteristics of 8697 patients with COVID-19 in China: a meta-analysis

Abstract: Meta-analysis estimates, given named study is omitted Lower CI Limit 0.86 Wu J[57] Xu YH[47] Xu X[46] Li KH[44] Xu s[41] Cheng KB[37] Li JS[35] Fang XW[62] Wang T[61] Zhang X[64] LI Y Y[13] Sun HY[15] Lu YF[17] Xiang TX[24] Xue HH[26] Gong X[27] Yuan J[29] Xiong J[31] Chen X[32] Zhou. YS[34] Song ZY[36] Cheng JL[39] Han J[40] Yang WJ[48] Xu XW[49] Wang D[51] Liu K[52] Huang CL[53] Guan W[55] Bernhem A[56] Shi HS[58] Zhou SC[60] Zhou F[8]on June 9, 2020 by guest. Protected by copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
118
7
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 37 publications
13
118
7
12
Order By: Relevance
“…Bilateral lung in ltrates (76%) was the most common radiological nding reported in older patients. These ndings had a similar WPP to that reported in other age groups (33,37,43).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Bilateral lung in ltrates (76%) was the most common radiological nding reported in older patients. These ndings had a similar WPP to that reported in other age groups (33,37,43).…”
Section: Discussionsupporting
confidence: 89%
“…As compared to the other studies (33,34,37,43,44), fever and cough had similar WPP, however, dyspnoea was found to be more prevalent in older patients as compared to the younger ones. Similarly, though diarrhoea has been noted as the most common gastrointestinal symptom in other studies (33,43) too, it has comparatively higher WPP in older population. It is important to note that gastrointestinal symptoms are common in older population, and patients and physicians should keep a low threshold of suspicion for COVID 19 even in the absence of typical symptoms.…”
Section: Discussioncontrasting
confidence: 38%
“…We identified 96 studies of COVID-19-related myalgia. After exclusion of descriptive reviews, data in other than English language, and duplicate studies, we selected 13 studies and 2 meta-analysis comprising of 10 and 55 studies, respectively (Table 1) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Search Resultsmentioning
confidence: 99%
“…Patients diagnosed before January 31 had higher prevalence of fever and cough. The authors concluded that as the pandemic grew, the prevalence of atypical symptoms increased [15]. In a study of olfactory and gustatory function in COVID-19 patients by Lechien et al, more than 50% patients had myalgia [76].…”
Section: Myalgiamentioning
confidence: 99%
“…Therefore, a clinical definition of COVID-19 is not reliable and laboratory confirmation of SARS-CoV-2 is currently advised for confirmation [4]. As asymptomatic patients tested positive for SARS-CoV-2, the lack of test capacity resulted in a lack of knowledge of the underlying true infection risk [5,6]. Since then, test capacities have been upscaled, but there is still an urgent need for reliable and cost-effective high-throughput testing methods, specifically as regulations are currently easing and loci of rapid spread need to be detected as early as possible, to avoid uncontrolled viral spread.…”
Section: Introductionmentioning
confidence: 99%